Soil chemical properties affected by cover crops under no-tillage system - Nascente, Adriano Stephan; Stone, Luis Fernando; Crusciol, Carlos Alexandre Costa (Universidade Federal de Viçosa, 2015)
The use of cover crops in no-tillage systems (NTS) can significantly improve the soil's fertility. Thus, a study was performed to evaluate changes in chemical properties of soil caused by cover crops in a no-tillage system. The field experiment consisted of the following crop rotation: cover crops/rice/cover crops/rice. The experimental design was in randomized blocks with three replications. Treatments consisted of four cover crops (Brachiaria brizantha(Hochst. ex A. Rich.) Stapf. cv. Marandu, Brachiaria ruziziensis R. Germ. and C.M. Evrard, Panicum maximum Jacq. cv. Colonião, and Pennisetum glaucum(L.) R. Br. cv. BN-2) and fallow (control treatment). Soil samples were collected at the beginning of the summer crop in Oct 2007, Oct 2008 and Oct 2009 at 0-5 cm soil depth. The use of cover crops provided for a significant increase in the level of nutrients, soil organic matter, cation exchange capacity, and base saturation in the soil. Soil fertility improved from the first to second year with the growing of cover crops. The soil under cover crops P. glaucum, B. ruziziensis, and B. brizantha showed higher fertility than the area under fallow.

O uso de plantas de cobertura no sistema de plantio direto (SPD) pode melhorar significativamente a fertilidade do solo. Assim, um estudo foi realizado para avaliar as alterações nas propriedades químicas do solo causadas pelas culturas de cobertura em sistema de plantio direto. O experimento de campo consistiu na rotação das seguintes culturas: plantas de cobertura/ arroz/ plantas de cobertura/ arroz. O delineamento experimental foi em blocos casualizados com três repetições. Os tratamentos consistiram de quatro espécies de plantas de cobertura (Brachiaria brizantha(Hochst. ex A. Rich.) Stapf. cv. Marandu, Brachiaria ruziziensis R. Germ. and C.M. Evrard, Panicum maximum Jacq. cv. Colonião and Pennisetum glaucum(L.) R. Br. cv. BN-2) e pousio (tratamento controle). As amostras foram coletadas no início da safra de verão, em outubro de 2007, 2008 e 2009, a 0-5 cm de profundidade. O uso de plantas de cobertura proporcionou aumento significativo na concentração de nutrientes, matéria orgânica do solo, capacidade de troca catiônica e saturação por bases. A fertilidade do solo melhorou do primeiro para o segundo ano com o cultivo de plantas de cobertura. O solo sob as plantas de cobertura P. glaucum, B. ruziziensis e B. brizantha apresentou maior fertilidade do que a área mantida sob pousio.
Propriedades químicas do solo afetadas por plantas de cobertura no sistema plantio direto
Keywords: Brachiaria brizantha(Hochst. ex A. Rich.) Stapf. cv. Marandu; Brachiaria ruziziensis R. Germ. and C.M. Evrard; Panicum maximum Jacq. cv. Colonião; Pennisetum glaucum(L.) R. Br. cv. BN-2; soil management; Brachiaria brizantha(Hochst. ex A. Rich.) Stapf. cv. Marandu; Brachiaria ruziziensis R. Germ. and C.M. Evrard; Panicum maximum Jacq. cv. Colonião, Pennisetum glaucum(L.) R. Br. cv. BN-2; manejo do solo